Beyond Bilateral: The Constitutive Dimensions of Strategic Partnership between Japan and Thailand - Salsabila Nurul Falah; Muhammad Sigit Andhi Rahman (Laboratorium Hubungan Internasional, FISIP, Universitas Jenderal Soedirman, 2022)
This article discusses bilateral state cooperation that was developed, with the agreement of both states, into a more comprehensive and long-term partnership, known as a Strategic Partnership. The dynamics in the bilateral relationship between these states, then become an attraction to further analyze the Japan-Thailand strategic partnership. The focus in this article is on the function of the strategic partnership, the roles of the two actors, and viewing it in a constitutive dimension. The author uses qualitative research using primary and secondary data in analyzing. The relationship and interactions between Japan and Thailand are analyzed on three levels: international, bilateral and individual, using the concept of strategic partnership as a social interaction between global actors and the role-playing that occurs. By observing from the perspective of both actors, the authors argue that the strategic partnership agreed upon by Japan and Thailand acts as an agency that facilitates self-conception to maintain their position, status and role in the international system.